THE EFFECT OF PATIENT SAFETY CULTURE AND INCIDENT REPORTING ON THE OCCURRENCE OF PATIENT FALLS - Penty Yuni Priyanda; Kosasih (RADJA PUBLIKA, 2026)
Patient falls are one of the most common adverse events in healthcare settings and have significant impacts on patient safety and quality of care. This study aims to analyze the effect of patient safety culture and incident reporting on the occurrence of patient falls at Hospital X. The research used a quantitative approach with a cross-sectional design. The population consisted of healthcare workers involved in patient care, with a sample selected using purposive sampling. Data were collected through structured questionnaires and analyzed using multiple linear regression. The results showed that patient safety culture has a significant negative effect on patient falls, indicating that a stronger safety culture contributes to reducing fall incidents. Incident reporting also has a significant negative effect, suggesting that effective reporting systems help in identifying and preventing fall occurrences. Simultaneously, patient safety culture and incident reporting have a significant effect on patient falls, as indicated by the F-test results. The coefficient of determination (R²) shows that both variables explain 32.1% of the variation in patient falls.